2019
DOI: 10.1038/s41559-019-0809-2
|View full text |Cite
|
Sign up to set email alerts
|

Widespread inhibition of daytime ecosystem respiration

Abstract: The global land surface absorbs about a third of anthropogenic emissions each year, due to the difference between two key processes: ecosystem photosynthesis and respiration. Despite the importance of these two processes, it is not possible to measure either at the ecosystem scale during daytime. Eddy-covariance measurements are widely used as the closest ‘quasi-direct’ ecosystem-scale observation from which to estimate ecosystem photosynthesis and respiration. Recent research, however, suggests that current e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 83 publications
7
120
0
Order By: Relevance
“…It is likely that in using this gap filling and partitioning methods, we overestimated the temperature sensitivity of gap filled NEE, and that we also overestimated or underestimated R eco due to the inhibition of respiration during light conditions, particularly at daily scales. However, annual estimates, as reported in this study, are less affected by this phenomena as recently reported (Desai et al, ; Keenan et al, ).…”
Section: Methodssupporting
confidence: 71%
“…It is likely that in using this gap filling and partitioning methods, we overestimated the temperature sensitivity of gap filled NEE, and that we also overestimated or underestimated R eco due to the inhibition of respiration during light conditions, particularly at daily scales. However, annual estimates, as reported in this study, are less affected by this phenomena as recently reported (Desai et al, ; Keenan et al, ).…”
Section: Methodssupporting
confidence: 71%
“…At FLUXNET sites night-time CO 2 advection and storage could cause underestimation of night-time CO 2 fluxes (Aubinet et al, 2012;McHugh et al, 2017;van Gorsel et al, 2009) and thus underestimate GPP using the night-time NEE flux partitioning method. On the contrary, it has been suggested that FLUXNET GPP estimated from the night-time partitioning method (Reichstein et al, 2005) is overestimated as it ignores the effects of light inhibition of leaf respiration (Keenan et al, 2019;Wehr et al, 2016) by on average 7 % across FLUXNET sites (Keenan et al, 2019). But it should be noted that this value may not be globally representative due to sizable variations between ecosystems and leaf area.…”
Section: Mean Annual Gross Primary Productivitymentioning
confidence: 99%
“…Our results using both partitioning approaches were quantitatively similar, and we observed a strong relationship between annual impact calculated with either daytime-partitioned or nighttime-partitioned data (figure S1, p < 0.0001, r 2 = 0.61). Thus, we focused on daytime-partitioned data since (1) nighttime-partitioned data can have negative values for GPP which slightly skew our calculations of impact, and (2) the daytime approach has recently been shown to be less prone to biases in flux partitioning related to light inhibition of respiration during the day (Keenan et al 2019), which becomes especially important since our analysis was only conducted on daytime data. Additionally, our results were the same after omitting any medium or poor quality gap-filled data (a quality flag of >1 in the FLUXNET2015 dataset, figure S2, p < 0.0001, r 2 = 0.87), indicating that FLUXNET gap-filling algorithms were unlikely to have caused hot moments in GPP.…”
Section: Sensitivity Analysis: Robustness Of Results To Post-processimentioning
confidence: 99%